5 - Joint Ownership of family land in Uganda: Examining the responses, challenges and policy implications - Robert Kabumbuli (African Sociological Review, 2016)
Many widows and orphans in get dispossessed of family land after the death of the head of household, but this could be countered by registered joint ownership of the land. Based on a study of two districts in Uganda, this paper examines the local responses, challenges and policy implications of joint ownership. Over 260 households, and a variety of key informants, were interviewed. The majority of respondents, especially women, agreed that joint ownership of family land is useful, arguing that it provides family security and enhances marital stability. Those who opposed joint ownership argued that marriage itself is unstable, and there is no trust between the spouses. In practice however, the family land is mostly male-owned. Most households do not have any ownership documents, and this is a challenge because joint ownership needs to be registered in order to be legally binding. The growing commercialization of land is also a challenge since it makes individual ownership more preferable. Joint ownership lacks strong support among both men and women, it is constrained by cultural beliefs and practices, and the institution of marriage in which it is anchored is getting weaker. Therefore in order to be effective, any policies and strategies for securing the interests of the family members in the family land must take account of these challenges.